Bemisia tabaci (Hemiptera: Aleyrodidae): evaluation of leaf trichome density based resistance on several soybean varieties - Murgianto, Fitrah; Hidayat, Purnama; Triwidodo, Hermanu (Universitas Lampung, 2023)
The whitefly Bemisia tabaci (Gennadius) is one of the important soybean pests which can reduce production up to 80 %. Soybean defense mechanism against B. tabaci is affected by the physical characteristics of the leaf surface, e.g. leaf thickness, density of trichomes, and sticky glandular trichomes. The objective of this research was to investigate B. tabaci population – trichome density relationship on ten soybean varieties. The experiment was carried out in Ngale Station, Ngawi District, East Java. The tested soybean varieties were Anjasmoro, Demas 1, Dena 1, Dering 1, Devon, Detam 3, Dewah, Gema, Grayak 1, and Wilis. The experiment was done by completely randomized design with three replications. Observation on the whitefly population was conducted weekly from 2 until 10 weeks after planting on 23 sample plants in each plot. The result showed that Devon was the variety with the highest population levels of B. tabaci, 10.89 (eggs), 14.48 (nymphs) individuals per leaf, respectively. The population of B. tabaci was affected by trichomes density. Devon was the highest density of trichomes (613.7 hairs per cm2). The density of trichomes and the number of whitefly eggs and nymphs relationship were significant (R2= 0,78 (egg) and 0.84 (nymph), n= 10, ?= 1 %, F Value= 0.00157, respectively).